Optimizing condition-based maintenance decisions for equipment subject to vibration monitoring - Jardine, A.K.S; Joseph, T; Banjevic, D (Journal of quality in maintenance engineering, 1999)
The paper reports the development of an optimal maintenance program based on vibration monitoring of critical bearings on machinery in the food processing industry. Statistical analysis of vibration data is undertaken using the software package EXAKT to establish the key vibration signals that are necessary for risk estimation. Once the risk curve is identified using a proportional hazards model, cost data are then blended with risk to identify the optimal maintenance program. The structure of the decision making software EXAKT is also presented. Concludes that perhaps the most important benefit of the study was the realization by maintenance management that it is possible to identify key measurements for examination at the time of vibration monitoring - thus possibly saving on inspection costs.